TES KEPRIBADIAN BERBASIS WEB UNTUK MENENTUKAN JENIS PEKERJAAN SESUAI DENGAN KEPRIBADIAN SESEORANG - YESNI MALAU (Paradigma, 2015)
Placement of employees in the right position closely related premises performance keryawan the placement of appropriate employees will increase the motivation and productivity of work, a tool often used by psychologists to conduct personality tests, namely with The sixteen personality factor questionnaire (16 PF). Obstacles often faced by the team selectors if the data processing results of the personality test done conventionally is the length of time needed to process the data considering the number of participants selection. Creating an application personality tests web-based is a solution to these problems, which psychologists make the matter with The sixteen personality factor questionnaire (16 PF) then the participants answered all the questions that have been provided on the monitor and the results of data processing can be seen directly by the committee test , Data processing using personality tests web-based applications more effective and efficient as a result of more accurate data processing, in addition to the application of web-based personality test to avoid errors in the input data which is caused by human error factor.